A model for continued LVAD patient success: A 4‐year readmission‐free HeartMate 3 postoperative course. Issue 3 (2nd February 2021) - Stonebraker, Corinne; Lee, Andy; Siddiqi, Umar; Lupo, Sydney; Brownlee, Andrew R.; Yang, Benjamin; Combs, Pamela; Jeevanandam, Valluvan
Abstract: Unplanned readmissions frequently occur following the implantation of a durable left ventricular assist device (LVAD) due to complications such as gastrointestinal bleeding and driveline infection. There is a paucity of literature describing the incidence of unplanned readmission in patients with a HeartMate 3 (HM3) Left Ventricular Assist System. In this report, we present the successful outcome of a patient with an HM3 LVAD who has experienced no unplanned readmissions in the 4‐year post‐implant phase. To our knowledge, this is the longest readmission‐free case after HM3 implantation. A successful patient outcome was enabled by the use of the modular HM3 device, the postoperative prescription of beta‐blockers and omega‐3, the presence of strong social support, and open communication between the patient's caregivers and the LVAD team. Reducing the instance of unplanned readmission confers clinical benefits to the patient, as well as reducing the cost burden on the patient and the healthcare system.